A mulher-cineasta: da arte pela arte a uma estética da diferenciação - Catarina Pereira, Ana (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The history of cinema begins in the late 19th century, in heterogeneous European societies with a common patriarchal structure. Studying feminist proposals applied to the seventh art therefore entails a reflection on archetypes of femininity and the simultaneous denunciation of gratuitous objectifications motivated by gender. The doctoral thesis summarized here aimed to identify the process that dictated women’s transition from traditional secondary roles (in production, photography, editing, set design, and screenwriting) to filmmaking. We observe the abandonment of the role of the other—an indecipherable object to whom a poem, a gaze, or an attempt at understanding is dedicated—and an embrace of individuality. The thesis, defended on June 30th at the University of Beira Interior, thus sought to answer the initial question: "What are we talking about when we talk about Portuguese cinema directed by women filmmakers?"